Animation for Educating, Socializing, and Giving Understanding Characteristics of Malnourished Children - Al Husaeni, Dwi Fitria; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Teaching in Science, 2022)
This study aims to determine the effect of educational socialization using animation media on the level of understanding of the characteristics of malnourished children in the residents of Cigugur Girang Village, Parongpong, Indonesia. The study was conducted on 20 residents of the village of Cigugur Girang Parongpong, Indonesia. The age range of the respondents is 20-60 years. Respondents consisted of 3 men and 17 women. The research was conducted in 3 stages, namely (i) pre-test; (ii) education through animation media; and (iii) post-test. The results showed that the average pretest score was 73.5 and the post-test average was 94.75. The results of the comparison of the pretest and posttest showed an increase in respondents' knowledge after the action was taken. The results of the N-Gain calculation show that the average N-Gain value is 21% (N-Gain 40%) indicating that animation media as a way of educating the characteristics of malnourished children is not effectively used in the community. This is because the community's pre-test scores are quite good, so it can be seen that the knowledge of characteristics of malnourished children is already known by the community. As for the results of the calculation of the t-test, it is known that the t-count (-8.213) t-table (2.086) means that the post-test score of the students increased not significantly. With the completion of this research, it is hoped that more people will know about the characteristics of malnourished children. Thus, the phenomenon of malnourished children can be tackled earlier.